Extensive haplotype diversity in African American mothers and their cord blood units. Issue 1 (20th November 2012) - Tu, B.; Leahy, N.; Yang, R.; Cha, N.; Kariyawasam, K.; Hou, L.; Xiao, Y.; Masaberg, C.; Pulse‐Earle, D.; Maiers, M.; Ng, J.; Kurtzberg, J.; et al.
<x xml:space="preserve">Abstract</x> HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1 assignments were obtained for 374 pairs of African American mothers and their umbilical cord blood units (CBU) by DNA sequencing. An algorithm developed by the National Marrow Donor Program was used to assign 1122 haplotypes by segregation. Seventy percent of the haplotypes carried assignments at all five loci. In the remainder, alleles at various loci, most often DQB1 in 48% of the haplotypes with a missing assignment, could not be assigned due to sharing of both alleles by mother and CBU. There were 652 haplotypes carrying a unique combination of alleles at the five loci; the majority (74%) were singletons. Novel B∼C and DRB1∼DQB1 associations were observed. The results show the genetic diversity in this population and provide validation for a publically available tool for pedigree analysis. Our observations underscore the need for procurement of increased numbers of units in the national cord blood inventory in order to identify matching donors for all patients requiring hematopoietic stem cell transplantation.